Sunitinib Plus Erlotinib Versus Placebo Plus Erlotinib in Patients With Previously Treated Advanced Non-Small-Cell Lung Cancer: A Phase III Trial - Scagliotti G.V. (2014)
Purpose: Sunitinib plus erlotinib may enhance antitumor activity compared with either agent alone in non-small-cell lung cancer (NSCLC), based on the importance of the signaling pathways involved in tumor growth, angiogenesis, and metastasis. This phase III trial investigated overall survival (OS) for sunitinib plus erlotinib versus placebo plus erlotinib in patients with refractory NSCLC. Patients and Methods: Patients previously treated with one to two chemotherapy regimens (including one platinumbased regimen) for recurrent NSCLC, and for whom erlotinib was indicated, were randomly assigned (1:1) to sunitinib 37.5 mg/d plus erlotinib 150 mg/d or to placebo plus erlotinib 150 mg/d, stratified by prior bevacizumab use, smoking history, and epidermal growth factor receptor expression. The primary end point was OS. Key secondary end points included progression-free survival (PFS), objective response rate (ORR), and safety. Results: In all, 960 patients were randomly assigned, and baseline characteristics were balanced. Median OS was 9.0 months for sunitinib plus erlotinib versus 8.5 months for erlotinib alone (hazard ratio [HR], 0.922; 95% CI, 0.797 to 1.067; one-sided stratified log-rank P = .1388). Median PFS was 3.6 months versus 2.0 months (HR, 0.807; 95% CI, 0.695 to 0.937; one-sided stratified log-rank P =.0023), and ORR was 10.6% versus 6.9% (two-sided stratified log-rank P = .0471), respectively. Treatment-related toxicities of grade 3 or higher, including rash/dermatitis, diarrhea, and asthenia/fatigue were more frequent in the sunitinib plus erlotinib arm. Conclusion: In patients with refractory NSCLC, sunitinib plus erlotinib did not improve OS compared with erlotinib alone, but the combination was associated with a statistically significantly longer PFS and greater ORR. The incidence of grade 3 or higher toxicities was greater with combination therapy. © 2012 by American Society of Clinical Oncology.